10 things not to do in an interview - Swann, David; Sutherland, Paul; Video Education Australasia (Australia : Video Education Australasia, 2006)
This mockumentary takes a comical and refreshing look at what not to do in a job interview. The program follows a job seeker and interviewer as they bumble their way through an interview. It covers a range of issues involved in this unique situation. This program will arm jobseekers against making these 10 mistakes in their interview.
Executive producer, Mark McAuliffe ; senior producer, Richard Leigh ; camera, Peter Zakharov ; sound, Alex Gudimenko.
DVD format
Keywords: Employment interviewing; Interviewing -- Technique; Interviews -- Students; Job interviews; Interviewing